Social representations about the crime that minors are institutionalized in a re-education center of the city of Bogotá - Vargas Espinosa, Nancy Marina; Universidad Católica de Colombia, Bogotá Colombia, Centro Internacional de Educación y Desarrollo Humano-CINDE, Bogotá Colombia, Universidad Pedagógica Nacional, Bogotá Colombia (Universidad Santo Tomás, Colombia, 2010)
The general objective that this investigation had was to know the social representations that the underage boarders have in a closed institution of reeducation in Bogotá city, especially in the location stage. By the way, the methodology used was the discussion technique of the focal group and from the speech analysis it was set out the following categories of analysis: delinquency conceptualization, attribution of responsibility, legitimacy of criminal acts and future. The results that were analyzed according with those categories show that the social representations about delinquency are the result of its conceptualization from the consequences, assessment, origin, instrumentation and knowledge. The attribution of responsibility in delinquency focuses in itself in relationship with others in family, social life and the opportunities that society offers. The future prospect gets influenced in the levels: personal, institutional and social. Key words: social representations, crime, institutionalized children